RESEARCH OF HETEROGENEOUS CATALYTIC TRIACETINE TRAVSETERIFICATION BY ETHANOL - Білокопитов, Ю.В.; Вдовін, В.С.; Драч, О.М.; Огданська, О.А.; Новоселов, Є.Ф. (Science-based technologies, 2009)
It was shown that on the oxides of chromium, tungsten and zirconium that were coated on titan-aerosil substrate proceeds a reaction of triacetine transesterification by ethanol. It is shown that the degree of transformation of triacetine grows at catalyst surface acidity increase.